2021
DOI: 10.1109/tnsre.2020.3043831
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Muscle Synergy Analysis in Individuals With Knee Osteoarthritis During Gait

Abstract: To clarify whether there are any muscle synergy changes in individuals with knee osteoarthritis, and to determine whether muscle synergy analysis could be applied to other musculoskeletal diseases. Methods: Subjects in this study included 11 young controls (YC), 10 elderly controls (EC), and 10 knee osteoarthritis patients (KOA). Gait was assessed on a splitbelt treadmill at 3 km/h. A non-negative matrix factorization (NNMF) was applied to the electromyogram data matrix to extract muscle synergies. To assess t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 55 publications
(94 reference statements)
0
24
0
Order By: Relevance
“…In particular, simulated data have been used to assess the accuracy of NAIC with a controlled and varying number of muscle synergies, while the test on experimental data has been introduced to check if our criterion is able to give precise results in different tasks, experimental conditions and pre-processing steps. (12) and has been chosen to simulate bell-shaped physiological activations. The corresponding C profiles have then a length that is increasing when the number of synergies is higher in order to maintain separation across the different activations.…”
Section: Comparison With Other Model Selection Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, simulated data have been used to assess the accuracy of NAIC with a controlled and varying number of muscle synergies, while the test on experimental data has been introduced to check if our criterion is able to give precise results in different tasks, experimental conditions and pre-processing steps. (12) and has been chosen to simulate bell-shaped physiological activations. The corresponding C profiles have then a length that is increasing when the number of synergies is higher in order to maintain separation across the different activations.…”
Section: Comparison With Other Model Selection Criteriamentioning
confidence: 99%
“…Some papers have shown that the level of motor impairment in pathological conditions [10]- [12] and the evolution of functional recovery [13]- [16] are related to the number of synergies describing the motor control structure. Thus, the objective and accurate assessment of such a number is mandatory to guarantee the repeatability of the results and the applicability of the approach to a clinical environment.…”
mentioning
confidence: 99%
“…"Conclusion" section concludes the research. Sprains [29] Muscular dystrophy [30] Epilepsy [31] Examples Tendinitis [32] Spinal muscular atrophy [33] Alzheimer's disease [34] Osteoarthritis [35] Muscle fatigue [36] Parkinson's disease [37] Data preparation…”
Section: Introductionmentioning
confidence: 99%
“…Second, it supports clinicians make a more robust diagnosis by providing a computer-aided indicator and helps them effectively in monitoring patients' health conditions. Examples Sprains [3] Muscular dystrophy [4] Epilepsy [5] Tendinitis [6] Spinal muscular atrophy [7] Alzheimer's disease [8] Osteoarthritis [9] Muscle fatigue [10] Parkinson's disease [11] Machine learning (ML) and deep learning (DL) have been widely used for automatically identifying health issues [12][13][14][15][16][17]. For example, by using 3D motion analysis, support vector machines (SVM) were applied for Parkinson's disease classification in [18] from gait signals.…”
Section: Introductionmentioning
confidence: 99%